Dynamics of photoinduced instability in ferroelectric photorefractive crystals - Morozovska, A.N.; Obukhovsky, V.V.; Lemeshko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
In the paper we theoretically consider the dynamics of the inner field generated by recharging trap waves propagation and spatial-temporal features of the photoinduced light scattering caused by these phenomena in the ferroelectric photorefractive crystals under steady illumination by laser beam. The transverse instability of the interacting light beams plays an important role and both the photovoltaic and the diffusion mechanisms of carrier transfer are taken into account in the proposed theory. For the first time it has been shown that, due to the influence of transverse photovoltaic current and typical boundary conditions for inner field, among all possible scenarios of transverse instabilities the boundary circle will be realized in the perfect crystal. Due to this phenomenon the periodical, quasi-periodical or aperiodical photoinduced light scattering appear in the system, depending on the structure of growth non-homogeneities and the character of photoinduced fluctuations caused by them. The correlation between the structure of scattering light waves and the type of these fluctuations has been considered in details for ilmenites. The great attention has been paid to the description of the optical autowaves generation and dynamic halo scattering in these materials. All the main theoretical results are in a good agreement with the available experimental data.